End-Of-Life Care in a Long-Term Intensive Care Unit - Horáčková, Kateřina; Portyšová, Šárka; Sládek, Karel; Kopecký, Michal; Pavlik, Vladimir (ST ELIZABETH UNIV HEALTH & SOCIAL WORK BRATISLAVA, 2023)
Background: The paper details the last day of the life of a selected group of terminal patients in a long-term intensive care unit in 2020 and 2021. Methods: The study comprises descriptive evaluation research focusing on retrospective monitoring and detailed documentation of predefined indicators based on a developed evaluation form. The aim of this analysis of the medical records was to assess the care provided to the terminal patient in the long-term intensive care unit in relation to the recommendations in the field of palliative care. Results: The main outcome of the research is that palliative care or palliative approach in the particular ward is lacking. Patients are thus burdened with many invasive diagnostic and therapeutic interventions at the end of life, which usually do not bring any benefit to the patient. The findings include frequent measurements of physiological functions, collection of biological material, administration of antibiotics and infusion therapy, most often via a venous catheter, preventive positioning and active rehabilitation, and the absence of psychosocial and spiritual care. Conclusion: The research confirms the necessity of implementing palliative care or its principles into patient care in the department of long-term intensive care. This is possible with the support of senior staff, the involvement of all members of the nursing team, and the development of valid standards or recommendations in the care of terminal patients. The situation would also be helped by the presence of a palliative care team throughout the hospital.
Péče o umírající pacienty na oddělení dlouhodobé intenzivní péče
Keywords: Long-term intensive nursing care; Terminal patients; End-of-life care; Palliative care; Dying